RELEVANCE OF CORPORATE GOVERNANCE MODELS IN COMPANIES DEVELOPMENT, IN CONTEXT OF THE GLOBAL CRISIS - LUMINIŢA CECILIA CRENICEAN (Challenges of the Knowledge Society)
Although the existing confusion regarding the concept of corporate governance persists, its role on sustainable maximize corporate values and providing high performance is undeniable. Moreover, the test of a corporate governance effectiveness model is the measurement in which it succeed to achieve the main objective, namely, that the company's perspective to maximize value to shareholders. In the economic crisis, it requires that by those systems in which companies are managed and controlled has to interact directly with social responsibility and business ethics held by those entities. It is expected that corporate managers have an efficient economic behavior, different from that of members of governments and economic decline that records do not meet current socio-economic situation